L’intelligence artificielle au service du multilinguisme : quels enjeux pour le français et l’italien ? - Cennamo, Ilaria; Mattioda, Maria Margherita (mediAzioni, 2025)
This contribution aims to analyse the impact of artificial intelligence (AI) on European integration, namely on multilingualism and on linguistic diversity. Our analysis will be developed following a pedagogical perspective concerning the study of the impact of AI tools on our students. This article presents the first results of a series of experimental activities in higher education, in the field of foreign languages and translation learning, with the aim to raise the awareness of students and organizations with respect to linguistic variation and multilingualism. Our results concern the French and Italian languages.